Enhancing Students’ Listening Comprehension through Animated Videos: A Pre-Experimental Study at MA Muhammadiyah Padaelo - Ayu, Sulfiana; Chandra, Ade; Bahnar, Siti Hardiyanti (Jurnal Edukasi Saintifik, 2024)
This study investigates the effectiveness of animated videos in improving students’ English listening comprehension at Madrasah Aliyah (MA) Muhammadiyah Padaelo. The research was conducted using a quantitative pre-experimental design involving 14 second-grade students during the 2024/2025 academic year. Data were collected through pre-test and post-test listening assessments and analyzed using descriptive and inferential statistics. The findings revealed a substantial increase in students’ average score—from 49.35% on the pre-test to 85% on the post-test—indicating significant improvement in listening comprehension after the use of animated videos. The results suggest that animated videos provide dual cognitive and affective benefits: they enhance understanding through visual and auditory integration and increase motivation by creating engaging, contextual learning experiences. These findings are consistent with Mayer’s Multimedia Learning Theory and Krashen’s Affective Filter Hypothesis, which highlight how well-designed multimedia can support both comprehension and confidence. The study concludes that animated videos are an effective supplementary medium for improving English listening skills among EFL learners.